2016
DOI: 10.1016/j.jpeds.2015.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Weight Status in the First 2 Years of Life and Neurodevelopmental Impairment in Extremely Low Gestational Age Newborns

Abstract: Objective To examine the extent to which weight gain and weight status in the first 2 years of life relate to the risk of neurodevelopmental impairment in extremely preterm infants. Study Design In a cohort of 1070 infants born between 23 and 27 weeks’ gestation, we examined weight gain from 7-28 days of life (in quartiles) and weight z-score at 12 and 24 months corrected age (in categories: <−2; ≥−2, <−1; ≥1, <1; ≥1) in relation to these adverse neurodevelopmental outcomes: Bayley-II mental development inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Further studies will be necessary to clarify the associations of later weight gain with better long-term neurodevelopmental outcomes. 27 BPD has been identified as an independent risk factor for the development of long-term neurodevelopmental impairments, including cerebral palsy and developmental delays, even in the absence of catastrophic brain injury. [28][29][30] In preclinical studies in newborn rats, 31 the intratracheal transplantation of MSCs simultaneously attenuated both hyperoxic lung and brain injuries, and the extent of neuroprotection was closely linked with that of pulmo-protection.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will be necessary to clarify the associations of later weight gain with better long-term neurodevelopmental outcomes. 27 BPD has been identified as an independent risk factor for the development of long-term neurodevelopmental impairments, including cerebral palsy and developmental delays, even in the absence of catastrophic brain injury. [28][29][30] In preclinical studies in newborn rats, 31 the intratracheal transplantation of MSCs simultaneously attenuated both hyperoxic lung and brain injuries, and the extent of neuroprotection was closely linked with that of pulmo-protection.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 118 papers, 76 did not mention that the GMFCS was developed specifically for use with children with CP or discuss its measurement properties . Twenty noted that the GMFCS was created for children with CP but did not justify its application to their condition/clinical description .…”
Section: Resultsmentioning
confidence: 99%
“…In 38 studies, the five GMFCS levels were collapsed into two or three broader groups (e.g. levels I, II, and III combined under the title of ‘ambulatory’ participants and levels IV and V combined under the title of ‘non‐ambulatory’ participants) . In one study involving children with CP, closed‐head injury, learning disability, or developmental delay, merging of levels (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an example of "reverse causation," which refers to situations where an antecedent is a consequence rather than a cause of illness. [51,[112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129] Another example has occurred in some studies that have found that people whose weight (or body mass index) is low were at heightened risk of death. [130] Low weight can be a consequence of disease that results in a loss of appetite.…”
Section: Coffee Consumption Changes During Early Pregnancymentioning
confidence: 99%